Pengaruh Faktor Individu Terhadap Kinerja Pegawai - Fefi Aryani Kuswandi; Eka Diah Kartiningrum (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
The performance of human resources in the health sector is useful in supporting the successful implementation of health programs and services in the community. individual factors are one of the factors that play a role in supporting employee performance. The purpose of this study was to analyze the influence of individual factors on employee performance at the Mojokerto District Health Office.This study used a cross sectional design with a sample size of 93 ASN and P3K employees who had been selected based on inclusion criteria. The individual factors studied include the latest education, length of service, commitment to the organization, desire to achieve, cooperation, proactivity, and discipline, Performance variables are measured based on supervisor assessments. Data was collected by questionnaire and then analyzed using Structural Equation Modeling (SEM). The results showed that the performance of most employees was high according to superiors. While on individual factors, most respondents have a bachelor's degree (52.7%), have worked for less than 5 years (61.3%), have had a negative work commitment (55.9%), a positive desire for achievement (52.7%), negative cooperation (51.6%), have a proactive nature in the negative category (51.6%), and have good discipline (71.3%). The results of SEM analysis show that there is an influence of individual factors (with indicators of commitment to the organization, desire to achieve, cooperation, proactivity, and discipline) (pvalue = 0.000) and organizational factors (rewards, facilities & infrastructure, supervision, supervisor support) (pvalue = 0.029) on employee performance (R2 = 0.160). Individual factors affect employee performance. The more positive individual factors, the better employee performance. Therefore, to increase the desire for achievement, cooperation, commitment and proactive attitude of employees towards performance, the Mojokerto District Health Office should often hold outbound events and competency training every year